Exploratory Seismic Geophysical Study of the Khanuqah Structure Area - Al Karadaghi, Salar S. Hasan (Journal of Petroleum Research and Studies, 2022)
Khanuqah structure area carried as the geophysics exploration study of Jeribe Formation target, the area located in the north of Iraq within Salah Aldeen Governorate, has been used geophysical data represented by 2D seismic lines were executed as exploratory surveys of 27 seismic lines, the data interpretations used by Petrel software (version 2018) based on the required aims, which are determined to achieve an update the structural model in Jeribe Fn. as a gas reservoir. The results show the Khanaqah structure includes five domes, the general direction of the structure axis is northwest-southeast, a gradient of its slope from the northwest structurally higher to the southwestern part structurally lower, the southeastern part of the study area is an open basin that increases the level of depth lines relative to the mentioned part. Seismic sections showed at the locations of structural domes the phenomenon of inter-spacing of seismic reflectors as tuning phenomena in reservoirs within Jeribe Fn. reservoir which is a direct index of the gas presence. To ensure tracking of extensions phenomena as a director for a gas presence, the seismic interpretations used a new technique by convert 2D seismic lines to 3D seismic cube through the reflections specifications publication of the khanaqah area, that shows the concerning of gaseous presence in the Khanaouqa-1 well and its disappearance in the Khanaouqa-2 well, it indicates the relationship between the location of the two wells at the structure, since Khanaouqa-1 well is structurally shallower than the Khanaouqa-2 well, which means that the well of Khanaouqa-2 is outside the scope of the gas patch, this was confirmed by the 3D seismic cube derived that showed the phenomenon presence on the site of Khanoqa-1 and did not appear in Khanoqa-2. Due to the importance of developing the Khanuqah structure as a worthy gas field, the research recommended drilling an exploratory well at the location of dome- B, whose coordinated in the study area penetrating the Euphrates Fn. bearing in mind that Khanuqa-1 did not locate on the center site of the domes nor on the center site of the direct phenomenon as evidence of the gas existence.